2019
DOI: 10.1186/s12906-019-2467-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a combination of herbal extracts (modified Ojayeonjonghwan (Wuzi Yanzong wan)) on partial urethral obstruction-induced detrusor overactivity in rats: impact on the nitric oxide pathway and oxidative stress

Abstract: sBackgroundWe investigated the effects of a berry mixture formula (modified Ojayeonjonghwan (Wuzi Yanzong Wan, MO formula) on detrusor overactivity (DO).MethodsThe MO formula consisted of 5 seeds obtained from 5 types of berry plants. Twenty-four Sprague-Dawley rats were randomly assigned to four groups: sham-operated (control), partial urethral obstruction-induced DO (DO group), 0.03 mg/kg solifenacin-treated DO (solifenacin group) and 200 mg/kg MO formula -treated DO (berry mixture). The control and overacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…Outcomes of multiple pre-clinical and clinical studies suggest an existence of association between the pathogenesis of OAB and oxidative stress (Speich et al, 2020), activation of immune system, and increased urinary secretion of neurotrophins (Bhide et al, 2013), which was partially also recorded in our experiments. Elevated values of MAL, 3-NIT, IL-1β, IL-6, and TNF-α were observed in patients and laboratory animals with signs of OAB and bladder inflammation (Gonzalez et al, 2015;Ding et al, 2017;Bae et al, 2019;Barut et al, 2019). Raised urinary NGF and BDNF values were detected in patients with DO (Frias et al, 2011) and in OAB patients (Antunes-Lopes and Cruz, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…Outcomes of multiple pre-clinical and clinical studies suggest an existence of association between the pathogenesis of OAB and oxidative stress (Speich et al, 2020), activation of immune system, and increased urinary secretion of neurotrophins (Bhide et al, 2013), which was partially also recorded in our experiments. Elevated values of MAL, 3-NIT, IL-1β, IL-6, and TNF-α were observed in patients and laboratory animals with signs of OAB and bladder inflammation (Gonzalez et al, 2015;Ding et al, 2017;Bae et al, 2019;Barut et al, 2019). Raised urinary NGF and BDNF values were detected in patients with DO (Frias et al, 2011) and in OAB patients (Antunes-Lopes and Cruz, 2019).…”
Section: Discussionmentioning
confidence: 97%
“…With the development of pharmacology research, numerous therapeutic components derived from herbal extracts have been identified [30,31]. Sesquiterpene lactones are a large family of compounds which have been shown to exhibit antimicrobial, antitumor, and anti-inflammatory effects [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…M2, particularly M2c, can induce CD4 + CD25 + Fxop3 + Tregs and can maintain the immunosuppressive function of Tregs unimpaired, thereby contributing to the resolution of inflammation and tissue repair [ 34 ]. Remarkably, with the significant progress achieved in pharmacology research, numerous therapeutic components isolated from herbal extracts demonstrate anti-inflammatory curative effects [ 38 , 39 ]. One of these compounds, Smiglaside A, promotes M2 polarization while inhibiting M1 polarization, likely mediated by the AMP-activated protein kinase (AMPK) and peroxisome proliferator activated receptor gama (PPARγ) signaling pathways [ 40 ].…”
Section: Macrophages and Acute Lung Injurymentioning
confidence: 99%